2009
DOI: 10.1063/1.3103336
|View full text |Cite
|
Sign up to set email alerts
|

Spin-resolved photoemission of a ferromagnetic Mn5Ge3(0001) epilayer on Ge(111)

Abstract: Here we present a study of the electronic structure of epitaxial ferromagnetic Mn 5 Ge 3 (0001) films on Ge(111) by means of x-ray absorption spectroscopy, x-ray photoelectron spectroscopy, and spin-resolved photoelectron spectroscopy. Spin-polarization (P ) value of +(15 ± 5)% at the Fermi energy (E F ) is measured with a photon energy of hν = 21.2 eV. Our findings are in contrast to recent band structure calculations predicting P = −41% at E F for the ferromagnetic bulk Mn 5 Ge 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…One important fact that makes the MnGe alloy interesting is that it shows magnetic properties at a temperature of ∼296 K. 2 The magnetic and structural properties of thin as well as thick Mn 5 Ge 3 films on Ge(111) grown by solid phase epitaxy have been studied by several groups. [2][3][4][5][6][7][8] Zeng et al 2,3 have reported that uniform Mn 5 Ge 3 films with a √ 3 × √ 3 periodicity, referred to as the Ge(111) surface, are produced when annealing as-deposited manganese between 300-650 • C, and that the formation of the √ 3 × √ 3 surface structure should be associated with the ordered Mn 5 Ge 3 phase. Sangaletti et al 5 provided evidence for the surface ferromagnetism in a thin metallic Mn/Ge(111) layer with a √ 3 × √ 3 surface structure.…”
Section: Introductionmentioning
confidence: 99%
“…One important fact that makes the MnGe alloy interesting is that it shows magnetic properties at a temperature of ∼296 K. 2 The magnetic and structural properties of thin as well as thick Mn 5 Ge 3 films on Ge(111) grown by solid phase epitaxy have been studied by several groups. [2][3][4][5][6][7][8] Zeng et al 2,3 have reported that uniform Mn 5 Ge 3 films with a √ 3 × √ 3 periodicity, referred to as the Ge(111) surface, are produced when annealing as-deposited manganese between 300-650 • C, and that the formation of the √ 3 × √ 3 surface structure should be associated with the ordered Mn 5 Ge 3 phase. Sangaletti et al 5 provided evidence for the surface ferromagnetism in a thin metallic Mn/Ge(111) layer with a √ 3 × √ 3 surface structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among other suitable materials Mn 5 Ge 3 presents all the prerequisite crite-15 ria necessary in spin devices: it is a well known ferromagnet with a magnetic ordering persisting up to the room temperature (T C = 297 K) [2], with an ex-perimental spin polarization of P = 15±5% [3], and it has been demonstrated that Mn 5 Ge 3 thin films could be grown epitaxially on a Ge (111) are grown by the so-called solid phase epitaxy (SPE) method which requires the co-deposition of Mn and C layers followed by annealing between 600 K and 920 K to activate the diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…It clearly shows another set of lattice structure different from the Ge matrix. Using the lattice spacing of the Ge as the reference, we calculated the observed lattice spaces of the cluster, which matched with the (002) and (010) atomic planes of the hexagonal Mn 5 Ge 3 phase [17][18]. Furthermore, it was confirmed that the Mn 5 Ge 3 (002) plane was parallel to the Ge (111) plane.…”
Section: Mn X Ge 1-x Thin Film Growth By Mbementioning
confidence: 90%